2022
DOI: 10.1007/s11250-022-03053-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance and ruminal and intestinal morphometry of Santa Inês sheep submitted to feed restriction and refeeding

Abstract: A study was carried out to evaluate the performance and ruminal and intestinal morphology of Santa Inês sheep subjected to feed restriction followed by refeeding. A total of 40 uncastrated lambs with an approximate age of 120 ± 15 days and mean body weight (BW) of 17.04 ± 1.18 kg were randomly divided into two groups of BW (20 and 25 kg of BW), which were subjected to different levels of feed restriction (0%, 25%, and 40% of feed restriction). For performance variables, six treatments were considered (0, 25%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Feed restriction programs have been used in post-weaning animals to improve feed efficiency and resistance to digestive system disorders, reducing carcass fat and production costs (Tumova et al 2021 ). Studies on feed restriction in pigs (Le Floc'h et al 2014 ), broilers (Van der Klein et al 2017 ), and sheep (Lima et al 2022 ) showed that animals can compensate the growth inhibition of feed restriction by improving feed efficiency. Moreover, feed restriction can be used to reduce morbidity and mortality in growing rabbits (Boisot et al 2003 ; Gidenne et al 2009 ; De Blas 2013 ), improve farm feed efficiency (Knudsen et al 2014 ; Birolo et al 2020a ), and reduce nitrogen emissions and environmental pollution (Birolo et al 2016 ; Birolo et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Feed restriction programs have been used in post-weaning animals to improve feed efficiency and resistance to digestive system disorders, reducing carcass fat and production costs (Tumova et al 2021 ). Studies on feed restriction in pigs (Le Floc'h et al 2014 ), broilers (Van der Klein et al 2017 ), and sheep (Lima et al 2022 ) showed that animals can compensate the growth inhibition of feed restriction by improving feed efficiency. Moreover, feed restriction can be used to reduce morbidity and mortality in growing rabbits (Boisot et al 2003 ; Gidenne et al 2009 ; De Blas 2013 ), improve farm feed efficiency (Knudsen et al 2014 ; Birolo et al 2020a ), and reduce nitrogen emissions and environmental pollution (Birolo et al 2016 ; Birolo et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%